2014
DOI: 10.1002/cncr.28630
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in physical activity among breast cancer survivors: Implications for breast cancer care

Abstract: Background Physical activity after breast cancer diagnosis is associated with improved survival. This study examines levels of and changes in physical activity following breast cancer diagnosis, overall and by race. Methods The Carolina Breast Cancer Study, Phase III, assessed pre- and post-diagnosis physical activity levels in a cohort of 1,735 women, aged 20–74, diagnosed with invasive breast cancer between 2008 and 2011 in 44 counties of North Carolina. Logistic regression and analysis of variance were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
78
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 32 publications
0
78
0
3
Order By: Relevance
“…Similar to the rest of the US population, breast cancer patients bear substantial comorbidity burdens, particularly as they age, with rates of severe comorbidities rising to over 30 % among women age 65 and older (Edwards et al 2013 ;Cho et al 2013 ). Rising rates of breast cancer risk factors, such as obesity, metabolic syndrome, and reduced levels of physical activity may further contribute to high rates of comorbidity in breast cancer patients (Guh et al 2009 ;Berrino et al 2014 ;Hair et al 2014 ). Improvements in breast cancer survival in recent decades, however, have primarily been experienced among cancer patients without comorbidities, and less so among those with moderate or severe comorbidities (Cronin-Fenton et al 2007 ;Land et al 2012a ).…”
Section: Introductionmentioning
confidence: 97%
“…Similar to the rest of the US population, breast cancer patients bear substantial comorbidity burdens, particularly as they age, with rates of severe comorbidities rising to over 30 % among women age 65 and older (Edwards et al 2013 ;Cho et al 2013 ). Rising rates of breast cancer risk factors, such as obesity, metabolic syndrome, and reduced levels of physical activity may further contribute to high rates of comorbidity in breast cancer patients (Guh et al 2009 ;Berrino et al 2014 ;Hair et al 2014 ). Improvements in breast cancer survival in recent decades, however, have primarily been experienced among cancer patients without comorbidities, and less so among those with moderate or severe comorbidities (Cronin-Fenton et al 2007 ;Land et al 2012a ).…”
Section: Introductionmentioning
confidence: 97%
“…Though limited, data from these reports suggest that they may be more likely to gain weight after diagnosis [14] and during treatment [15], and are less likely to meet physical activity or nutrition recommendations [1619]. In a recent review of 82 physical activity trials, Speck and colleagues (2010) [20] concluded that 76% of reviewed studies did not properly describe the sample characteristics and race was the factor most commonly overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, most studies evaluating post-diagnosis pa in cancer patients have involved survivors of breast and colorectal cancers. Those studies suggested that ethnicity 21 , social support 22,23 , and cancer-related beliefs 24 were influential factors.…”
Section: Introductionmentioning
confidence: 99%